Identification of potential protein biomarkers in sera of the elderly and their association with frailty status / Puvanesswaray Ramakrishnan - Puvanesswaray, Ramakrishnan (2018)
Early identification of frailty is of increasing importance as it may reduce the risk of adverse outcomes in older people. Potential biomarkers of frailty may be detected using proteomic applications that analyse serum samples of older subjects who are stratified according to their frailty status. This study is aimed at identifying potential biomarkers of frailty associated with non-frail, pre-frail and frail status in older subjects. Frailty status was determined using the Frailty Index. Blood samples taken from participants recruited from University Malaya Medical Centre were analysed using proteomic techniques. Enhanced expression of alpha-1-antitrypsin (A1AT), alpha-1B-glycoprotein (A1BG), haptoglobin (HAP), hemopexin (HPX), kininogen (KNG1) and leucine-rich alpha-2-glycoprotein (LRG) and reduced expression of apolipoprotein E (APOE) and isoform 2 of clusterin (CLU) were detected in sera of frail elderly when samples were subjected to 2-Dimensional Electrophoresis (2-DE) and analysed by densitometry. In the pre-frail elderly, KNG and A1AT showed increased in abundance levels. In glycoprotein analysis utilising CGB-lectin affinity blotting, LRG levels were significantly reduced in pre-frail subjects while HAP levels were significantly higher in the frail elderly relative to control non-frail subjects when pooled serum samples were subjected to CMB-AP conjugated lectin in western blot analysis. Enzyme-linked immunosorbent assay analysis showed serum A1AT concentration levels that were significantly higher (degree of fold change <1.5) while APOE was reduced in frail older adults compared with the non-frail, consistent with proteomic findings. This study suggests an association between frailty and certain proteins with their levels identified at different frailty status. The identification of these potential biomarkers of frailty may iv provides towards an understanding of frailty and identifies proteins which may contribute towards the early detection of frailty in older people.